We all fall down eaudiobook Living with addiction. - Sheff, Nic (2013)
In his follow-up to his bestselling memoir Tweak: Growing Up On Methamphetamines, Nic Sheff reveals a brutally honest account of a young person's struggles with relapse and rehab. In his bestselling memoir Tweak , Nic Sheff took readers on an emotionally gripping roller-coaster ride through his days as an addict. In this powerful follow-up about his continued efforts to stay clean, Nic writes candidly about eye-opening stays at rehab centers, devastating relapses, and hard-won realizations about what it means to be a young person living with addiction. By candidly revealing his own failures and small personal triumphs, Nic inspires readers to maintain hope and to remember that they are not alone in their battles. A group reading guide is included. Nic Sheff's Tweak , We All Fall Down , and his father's memoir about him ( Beautiful Boy ) are the basis of the film Beautiful Boy starring Steve Carell and Timothée Chalamet.